High frequencies of a favorable IL‐28B rs8099917 polymorphism and the clinical implications in patients with HCV in one multiracial area of Taiwan. Issue 10 (1st July 2017) - Cheng, Chun‐Han; Lin, Ching‐Chung; Chen, Huan‐Lin; Lin, I.‐Tsung; Wu, Chia‐Hsien; Lee, Yuan‐Kai; Wong, Ming‐Wun; Bair, Ming‐Jong
Abstract: There is a strong association between hepatitis C virus (HCV) treatment efficacy and the interleukin (IL)‐28B gene. However, the IL‐28B variant's distribution and potential role in the therapeutic response are not well established in Taitung, a racially diverse county in Taiwan. Here, we investigated the distribution pattern of IL‐28B rs8099917 and its influence on treatment efficacy. In this retrospective study, we enrolled 180 patients who had been treated with pegylated‐interferon plus ribavirin. Patients' general information, virological characteristics, IL‐28B status, laboratory results, treatment course, and outcome were analyzed. Of the patients enrolled, 56.7% were male, with a mean age of 54.11 years. A total of 24.4% of the population were indigenous people. The majority of patients had the favorable IL‐28B polymorphism (rs8099917 TT/TG/GG: 94.4%/5.6%/0%). The proportion of patients with the TT genotype seemed to be higher in indigenous patients. The rate of sustained virological response (SVR) among included patients was 73.0%. Univariate analysis showed that genotype non‐1, patients achieved rapid virological response (RVR), lower body mass index (BMI), and lower baseline HCV viral load were significantly associated with SVR. Multivariate analysis revealed that BMI <25 and RVR are the independent predictor of success treatment. In conclusion, the favorable IL‐28B rs8099917 polymorphism occurs in high frequency in this multiracial area, which might be important to help guide physicians and patients in their future clinical decisions.